Energy harvesting from plants using hybrid microbial fuel cells; potential applications and future exploitation - Greenman, John; Thorn, Robin; Willey, Neil; Ieropoulos, Ioannis (Frontiers in Bioengineering and Biotechnology, 2024)
Microbial Fuel Cells (MFC) can be fuelled using biomass derived from dead plant material and can operate on plant produced chemicals such as sugars, carbohydrates, polysaccharides and cellulose, as well as being 'fed' on a regular diet of primary biomass from plants or algae. An even closer relationship can exist if algae (e.g., prokaryotic microalgae or eucaryotic and unicellular algae) can colonise the open to air cathode chambers of MFCs driving photosynthesis, producing a high redox gradient due to the oxygenic phase of collective algal cells. The hybrid system is symbiotic; the conditions within the cathodic chamber favour the growth of microalgae whilst the increased redox and production of oxygen by the algae, favour a more powerful cathode giving a higher maximum voltage and power to the photo-microbial fuel cell, which can ultimately be harvested for a range of end-user applications. MFCs can utilise a wide range of plant derived materials including detritus, plant composts, rhizodeposits, root exudates, dead or dying macro-or microalgae, via Soil-based Microbial Fuel Cells, Sediment Microbial Fuel Cells, Plant-based microbial fuel cells, floating artificial islands and constructed artificial wetlands. This review provides a perspective on this aspect of the technology as yet another attribute of the benevolent Bioelectrochemical Systems.